Patterns of Teachers’ Occupational Well-Being During the COVID-19 Pandemic: Relations to Experiences of Exhaustion, Recovery, and Interactional Styles of Teaching - Pöysä, Sanni; Pakarinen, Eija; Lerkkanen, Marja-Kristiina (Frontiers in Education, 2021)
This study examined profiles of teachers’ occupational well-being during the COVID-19 pandemic. The data were collected from 279 Finnish primary school teachers during the spring of 2020. Four groups of teachers were identified by using Latent Profile Analysis: (1) teachers with mediocre stress and work engagement (34.4%); (2) teachers with mediocre stress and lowest work engagement (11.5%); (3) teachers with highest stress and work engagement (26.5%); and (4) teachers with lowest stress and highest work engagement (27.6%). The findings indicated that teachers’ occupational well-being was individually constructed, and there was a diversity with ways how negative and positive aspects of occupational well-being were drawn into patterns. The profile groups were further analyzed with respect to teachers’ experiences of emotional exhaustion, recovery from work, and interactional styles of teaching. The results revealed that during the first few months of the COVID-19 pandemic many teachers experienced occupational stress as well as some increase in stress due to the pandemic. In addition, the findings provided new insights concerning how teachers’ work engagement was perhaps not severely affected during the first few months of the pandemic, and on how different teaching styles were associated specifically with different aspects of occupational well-being.